Sustainability and efficiency analysis of 42 countries: Super SBM-DEA model and the GML productivity index with undesirable outputs - Amsalu K. Addis (Ecological Indicators, 2025)
The interplay of renewable energy, energy consumption, innovation, and labor dynamics is critical for balancing economic growth with ecological sustainability amidst climate change challenges. This study employs the Super SBM-DEA model and the Global Malmquist-Luenberger (GML) productivity index to analyze the sustainability and efficiency of 42 countries from 1995 to 2022, focusing on the trade-offs between economic growth, human development, and environmental performance. Using a set of input (renewable energy, energy consumption, labor force, and innovation) and output variables, the study evaluates how efficiently countries convert resources into desirable outputs (GDP and human development) while minimizing the undesirable output (CO2 emissions). The Super SBM-DEA model result reveals Brazil’s persistent ranking as the least efficient among 42 countries, with scores ranging between 0.919 and 0.972. This inefficiency stems from Brazil’s challenges in optimally managing inputs and undesirable outputs aligned with its development objectives. In contrast, Ireland, Italy, Saudi Arabia, and the US consistently achieve near-maximum efficiency scores, predominantly around 1.000, demonstrating effective resource utilization. The GML productivity index indicates stability, with scores ranging from 0.996 (Saudi Arabia and Turkey) to 1.010 (Latvia), and most countries clustering around 1, suggesting minimal fluctuations in productivity. Efficiency changes are slight, as evidenced by values near 1; Norway, Sweden, and Switzerland lead with scores of 1.002, while Estonia, Hungary, and Japan exhibit slightly lower scores (0.999). Estonia’s technological efficiency score of 1.010 indicates higher improvements in technology-driven productivity, reflecting wider trends in advancing economies. Conversely, Turkey’s low technological efficiency score of 0.995 suggests difficulties in technological enhancement. This study underscores the need for targeted policies to enhance resource efficiency, particularly in countries like Brazil, by improving management and minimizing CO2 emissions. It highlights the importance of fostering technological innovation in less efficient nations and integrating renewable energy sources into national grids for a greener future. The disparities in efficiency and productivity identified in our analysis have significant policy implications for national governments, particularly for those countries facing challenges in balancing economic and ecological goals. The contrasting performances among countries serve as a valuable guide for policymakers.